2006
DOI: 10.1121/1.2161431
|View full text |Cite
|
Sign up to set email alerts
|

The relative roles of vowels and consonants in discriminating talker identity versus word meaning

Abstract: Three experiments tested the hypothesis that vowels play a disproportionate role in hearing talker identity, while consonants are more important in perceiving word meaning. In each study, listeners heard 128 stimuli consisting of two different words. Stimuli were balanced for same/different meaning, same/different talker, and male/female talker. The first word in each was intact, while the second was either intact (Experiment 1), or had vowels ("Consonants-Only") or consonants wels-Only") replaced by silence (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 80 publications
8
67
1
1
Order By: Relevance
“…Bonatti et al (2005) suggested that consonants and vowels were more tied to word identification and grammar, respectively, in continuous speech. In addition, speech materials and language-specific vowel-consonant ratio would also impact the relative contribution of vowels and consonants in speech perception (e.g., Owren and Cardillo, 2006). One of the reasons for the difference between isolated-word (e.g., Owren and Cardillo, 2006) and sentence perception is that the sentence context itself strongly constrains lexical competition.…”
Section: Results Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Bonatti et al (2005) suggested that consonants and vowels were more tied to word identification and grammar, respectively, in continuous speech. In addition, speech materials and language-specific vowel-consonant ratio would also impact the relative contribution of vowels and consonants in speech perception (e.g., Owren and Cardillo, 2006). One of the reasons for the difference between isolated-word (e.g., Owren and Cardillo, 2006) and sentence perception is that the sentence context itself strongly constrains lexical competition.…”
Section: Results Inmentioning
confidence: 99%
“…In addition, speech materials and language-specific vowel-consonant ratio would also impact the relative contribution of vowels and consonants in speech perception (e.g., Owren and Cardillo, 2006). One of the reasons for the difference between isolated-word (e.g., Owren and Cardillo, 2006) and sentence perception is that the sentence context itself strongly constrains lexical competition. Hence listeners may retrieve or predict sentences' meaning by using a priori knowledge, language experience and contextual cues involved in a top-down processing.…”
Section: Results Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Vowel inherent spectral change has been found to be central for differentiating regional variations of American English (Jacewicz and Fox, 2013), and vowel spectra also effectively differentiate American, British, and Australian English (Ghorshi et al, 2008). Listeners are most sensitive to indexical information in vowels rather than consonants: they are more effective at discriminating between speakers based on vowels than consonants (Owren & Cardillo, 2006), and are more likely to notice when vowels, rather than consonants, are replaced with tokens from other speakers (Hertz et al, 2004;Hertz, 2006). If vowels are naturally more prone to slight differences across accents and speakers than consonants are, and listeners are sensitive to such differences, this could lead listeners to learn to treat vowels as though they have high meaningful variance.…”
Section: The Meaning Of Taumentioning
confidence: 99%
“…4-6; but see ref. 7). Across multiple studies, investigators have deleted parts of waveforms of sentences corresponding roughly to consonants or vowels and replaced them with noise.…”
mentioning
confidence: 99%